Drivers, Barriers and Key Success of Digital Transformation on SMEs: A Systematic Literature Review - Ni Putu Ari Krismajayanti; Gede Sri Darma; Luh Putu Mahyuni; Ida Ayu Oka Martini (JASF: Journal of Accounting and Strategic Finance, 2024)
Digital transformation represents a critical initial step for Small and Medium Enterprises (SMEs) in adapting to digitalization. This process involves technological innovations, efficient economic operations, and strategic initiatives to support SMEs. The SME sector holds significant importance as a cornerstone of national economic development. This study employs a systematic literature review to synthesize insights into the driving factors, barriers, and success strategies for SMEs undertaking digital transformation. The driving factors are categorized into individual, technological, environmental, and organizational contexts. Conversely, the barriers include challenges faced by individual business actors, as well as technical, environmental, organizational, and cultural constraints. The success of SMEs in this transformation depends on both internal and external factors. Internally, success is fostered through adequate knowledge and education on digitalization, the development of innovative business models, digital capabilities, organizational functions, culture, and effective human resource management. Externally, success depends on adapting to environmental shifts, building partnerships, and utilizing government regulatory support, which serves as a key driver of digital transformation for SMEs. These results imply that policymakers, SME practitioners, and SME stakeholders have to collaborate in overcoming challenges and seizing opportunities for SME digital transformation.